Humulone Modulation of GABAA Receptors and Its Role in Hops Sleep-Promoting Activity - Benkherouf, Ali Y.; Eerola, Kim; Soini, Sanna L.; Uusi-Oukari, Mikko (Frontiers in Neuroscience, 2020)
Humulus lupulus L. (hops) is a major constituent of beer. It exhibits neuroactive properties that make it useful as a sleeping aid. These effects are hypothesized to be mediated by an increase in GABAA receptor function. In the quest to uncover the constituents responsible for the sedative and hypnotic properties of hops, recent evidence revealed that humulone, a prenylated phloroglucinol derivative comprising 35–70% of hops alpha acids, may act as a positive modulator of GABAA receptors at low micromolar concentrations. This raises the question whether humulone plays a key role in hops pharmacological activity and potentially interacts with other modulators such as ethanol, bringing further enhancement in GABAA receptor-mediated effects of beer. Here we assessed electrophysiologically the positive modulatory activity of humulone on recombinant GABAA receptors expressed in HEK293 cells. We then examined humulone interactions with other active hops compounds and ethanol on GABA-induced displacement of [3H]EBOB binding to native GABAA receptors in rat brain membranes. Using BALB/c mice, we assessed humulone’s hypnotic behavior with pentobarbital- and ethanol-induced sleep as well as sedation in spontaneous locomotion with open field test. We demonstrated for the first time that humulone potentiates GABA-induced currents in α1β3γ2 receptors. In radioligand binding to native GABAA receptors, the inclusion of ethanol enhanced humulone modulation of GABA-induced displacement of [3H]EBOB binding in rat forebrain and cerebellum as it produced a leftward shift in [3H]EBOB displacement curves. Moreover, the additive modulatory effects between humulone, isoxanthohumol and 6-prenylnaringenin were evident and corresponded to the sum of [3H]EBOB displacement by each compound individually. In behavioral tests, humulone shortened sleep onset and increased the duration of sleep induced by pentobarbital and decreased the spontaneous locomotion in open field at 20 mg/kg (i.p.). Despite the absence of humulone effects on ethanol-induced sleep onset, sleep duration was increased dose-dependently down to 10 mg/kg (i.p.). Our findings confirmed humulone’s positive allosteric modulation of GABAA receptor function and displayed its sedative and hypnotic behavior. Humulone modulation can be potentially enhanced by ethanol and hops modulators suggesting a probable enhancement in the intoxicating effects of ethanol in hops-enriched beer.